1966
DOI: 10.1002/anie.196608961
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tellurophene and its 2,5‐Disubstituted Derivatives

Abstract: R Con v e r s i o I70 92-93/0.8 18 116/0.5 76 130/2 11 155/1 59 125-1 26/0.3 11 190-200/0.4 71 m.p. 87-88 18 58 155/3 27 135--139/1 -n?o D 1.5835 1.5941 1.5640 1.5645 1.6296 1.6630 --1.6004 1.5624 Chlorination (at room temperature without solvent) of compound (2.) does not, like that of ethyl pentachloro-1,3butadienyl ether, cause ether fission with formation of an acid chloride [31, but instead leads to a-chloroethyl pentachloro-1,3-butadienyl sulfide (4) (84 %, b.p. 119 '(72.2 mm,Reaction of the compound (2a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 2 publications
0
26
0
Order By: Relevance
“…They are rather stable solids, which can be crystallized from the usual organic solvents and from the melt without decomposition. Their melting point is considerably higher than that of the selenium-containing isologues, which are liquid at room temperature (Lucchesini, Bertini & De Munno, 1984); it is also higher than that of the tellurophene analogues (Mack, 1966). Low solubility and high melting point were also found for 1,2,5-telluradiazole, with respect to the selenium homologue (Bertini, Dapporto, Lucchesini, Sega & De Munno, 1984).…”
mentioning
confidence: 99%
“…They are rather stable solids, which can be crystallized from the usual organic solvents and from the melt without decomposition. Their melting point is considerably higher than that of the selenium-containing isologues, which are liquid at room temperature (Lucchesini, Bertini & De Munno, 1984); it is also higher than that of the tellurophene analogues (Mack, 1966). Low solubility and high melting point were also found for 1,2,5-telluradiazole, with respect to the selenium homologue (Bertini, Dapporto, Lucchesini, Sega & De Munno, 1984).…”
mentioning
confidence: 99%
“…433,456 Among many synthetic strategies towards unsaturated organotellurium compounds, the hydrotelluration of diynes is a highly efficient and stereoselective method for enynyl tellurides which are useful building blocks in modern chemistry. Since the first synthesis of tellurophene by the interaction of 1,3-butadiyne 1a and 1152 with Na 2 Te 1153 in methanol developed by Mack's in 1966, 457 the several papers describing hydrotelluration of diynes appeared [458][459][460][461][462][463][464][465][466][467][468] which was also covered by Detty 431 and Zeni. 446,469 In this chapter the recent development of functionalisation of diynes by tellurium compounds will be presented.…”
Section: Hydroselenation Of 13-diynesmentioning
confidence: 99%
“…6 Moreover it was demonstrated that tellurophene could be directly converted into the Te(IV) dibromide heterocycle 2 via treatment with elemental bromine (Scheme 1). The reverse of this process, re-reduction of 2 into the parent tellurophene (1), was also possible by addition of HSO 3 ¹ .…”
Section: Early Work On Tellurophene and Its Polymeric Analoguesmentioning
confidence: 99%
“…Polymer 14 was obtained with relatively high molecular weight (M n = 23.2 kDa) and had an optical band gap, determined from the onset of absorption, of 1.28 eV in orthodichlorobenzene. Solar cells consisting of a blend of 14 and PC 71 BM ( [6,6]-phenyl-C71-butyric acid methyl ester) as an active layer gave power conversion efficiencies (PCEs) as high as 4.4%. 23 The same group reported solar cells consisting of molecular donor molecules with capping benzotellurophene substituents, leading to elevated PCE values of up to 5.8%.…”
Section: New Routes To Tellurium Heterocycles and Post-functionalizatmentioning
confidence: 99%